1998
DOI: 10.1007/bf02815073
|View full text |Cite
|
Sign up to set email alerts
|

Dephosphorylation of tau during transient forebrain ischemia in the rat

Abstract: The effect of transient cerebral ischemia on phosphorylation of the microtubule-associated protein (MAP) tau was investigated using the rat four-vessel occlusion model. Phosphorylation of tau is proposed to regulate its binding to microtubules, influencing the dynamics of microtubule assembly necessary for axonal growth and neurite plasticity. In this study, tau was rapidly dephosphorylated during ischemia in the hippocampus, neocortex, and striatum. Dephosphorylation of tau was observed within 5 min of occlus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 56 publications
6
30
1
Order By: Relevance
“…5). Experimental data on cultured cells or animal models have demonstrated that tau proteins are transiently dephosphorylated but never hyperphosphorylated during ischemia and reperfusion or similar experimental conditions (Dewar and Dawson, 1995;Shackelford and Nelson, 1996;Burkhart et al, 1998;Shackelford and Yeh, 1998). It is therefore probable that tau protein in ischemic foci undergoes some pathological modifications to be visualized on immunohistochemistry, although these modifications are not necessarily related to phosphorylation and are indistinguishable from unmodified human tau protein on routine immunoblot, as we demonstrated on GCIs (Shibuya et al, 2003).…”
Section: Discussionsupporting
confidence: 51%
“…5). Experimental data on cultured cells or animal models have demonstrated that tau proteins are transiently dephosphorylated but never hyperphosphorylated during ischemia and reperfusion or similar experimental conditions (Dewar and Dawson, 1995;Shackelford and Nelson, 1996;Burkhart et al, 1998;Shackelford and Yeh, 1998). It is therefore probable that tau protein in ischemic foci undergoes some pathological modifications to be visualized on immunohistochemistry, although these modifications are not necessarily related to phosphorylation and are indistinguishable from unmodified human tau protein on routine immunoblot, as we demonstrated on GCIs (Shibuya et al, 2003).…”
Section: Discussionsupporting
confidence: 51%
“…In comparison, regulation of the 12E8 site appears to be less dependent on ATP/GTP levels. In rats, occlusion of the middle cerebral artery causes rapid dephosphorylation of tau as demonstrated by changes in the mobility or immunoreactivity of tau protein [20,38]. Dephosphorylation rate may depend on the specific phosphorylation site and localization of tau.…”
Section: Discussionmentioning
confidence: 98%
“…Rapid dephosphorylation of tau has been reported in post mortem rat and human brain tissues [17,18] indicating that phosphorylation state of tau is a very dynamic process. The effects of ischemia and reperfusion on tau metabolism have been studied in rats [19,20] and dogs [21] but not in gerbils. Yet gerbils are a long established model of reversible ischemia [22][23][24] used in a number of biochemical studies [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Although tau phosphorylation was not examined here, it is noteworthy that changes in tau phosphorylation have been observed during cardiac arrest-induced cerebral ischemia and reperfusion (Mailliot et al, 2000), transient forebrain ischemia in rats (Shackelford and Yeh, 1998), and in cortical slices subjected to hypoxia combined with glucose deprivation (Burkhart et al, 1998).…”
Section: Et Al 2001mentioning
confidence: 99%